Role of the DmpR-Mediated Regulatory Circuit in Bacterial Biodegradation Properties in Methylphenol-Amended Soils - Sarand, Inga (American Society for Microbiology, 2001)
Pathway substrates and some structural analogues directly activate the regulatory protein DmpR to promote transcription of the dmp operon genes encoding the (methyl)phenol degradative pathway of Pseudomonas sp. strain CF600. While a wide range of phenols can activate DmpR, the location and nature of substituents on the basic phenolic ring can limit the level of activation and thus utilization of some compounds as assessed by growth on plates. Here we address the role of the aromatic effector response of DmpR in determining degradative properties in two soil matrices that provide different nutritional conditions. Using the wild-type system and an isogenic counterpart containing a DmpR mutant with enhanced ability to respond to para-substituted phenols, we demonstrate (i) that the enhanced in vitro biodegradative capacity of the regulator mutant strain is manifested in the two different soil types and (ii) that exposure of the wild-type strain to 4-methylphenol-contaminated soil led to rapid selection of a subpopulation exhibiting enhanced capacities to degrade the compound. Genetic and functional analyses of 10 of these derivatives demonstrated that all harbored a single mutation in the sensory domain of DmpR that mediated the phenotype in each case. These findings establish a dominating role for the aromatic effector response of DmpR in determining degradation properties. Moreover, the results indicate that the ability to rapidly adapt regulator properties to different profiles of polluting compounds may underlie the evolutionary success of DmpR-like regulators in controlling aromatic catabolic pathways.